Structure of variation in enzyme activity in natural Drosophila melanogaster populations. - Pecsenye, K.; Saura, A. (Hereditas, 2002)
Enzyme activity variation was assessed in several isofemale lines originating from two Hungarian Drosophila melanogaster populations. Samples from each population were taken from from two villages; 8-9 isofemale lines were established from each village. The activities of ADH, alphaGPDH, IDH and 6PGDH were determined in the adults (in the F1 generation) and in the larvae (in the F3 generation) as well. Enzyme activities were measured on starch gel after electrophoresis. The activity of the enzyme was detected in a single individual and it was also possible to determine its genotype. The results showed that most of the variation occurred within sites for all four enzymes. This within site variation was more or less equally partitioned into within and between isofemale line (family) components. A smaller portion of variation was attributable to the differences between the populations. Nevertheless, adult alphaGPDH, and larval IDH and 6PGDH activities exhibited significant differences between the two populations. Variation in larval activities of all enzymes was higher than that of the adults, but 6PGDH had considerably higher variation in the adults. The greater variation in larval activities probably reflected the greater environmental variation in the microhabitat of the larvae compared to that of the adults. Larval activities of the investigated enzymes showed much stronger correlation than adult activities. The correlation pattern in the adults differed greatly between the two populations.